STRENGTHENING LOCAL BRAND COMPETITIVENESS: FACTORS DRIVING REPURCHASE OF KOPI TUKU - Widya Prameswara; Novan Yurindera (jfpublisher, 2025)
This research aims to determine whether there is a significant influence of price, product quality, and social media marketing on the repurchase decision of Kopi Tuku. The independent variables consist of price, product quality, and social media marketing, while the dependent variable is the repurchase decision. The research method used in this study is a quantitative method. The population in this study consists of all consumers of Kopi Tuku products in the Jabodetabek area. The sampling technique used in this research is nonprobability sampling, specifically purposive sampling, with a total of 200 respondents. Data analysis uses validity testing, reliability testing, descriptive analysis, multiple linear regression analysis, coefficient of determination (R²), F-statistic test (simultaneous test), and t-statistic test (partial test). Based on the F-statistic test results (simultaneous test), it can be concluded that price, product quality, and social media marketing simultaneously have a significant influence on the repurchase decision of Kopi Tuku. Based on the t-statistic test results (partial test), it can be concluded that price, product quality, and social media marketing partially have a significant influence on the repurchase decision of Kopi Tuku.